2015
DOI: 10.1111/ijcs.12262
|View full text |Cite
|
Sign up to set email alerts
|

Organic consumers’ preferences and willingness‐to‐pay for locally produced animal products

Abstract: In Germany, a large share of organic animal products is being produced with imported protein feedstuffs. Products labelled as ‘local’ are also often produced with imported feed. At the point of purchase, animal products are not usually labelled with any information on the feed that was used to produce it. Therefore, it remains unclear what consumers think about the use of imported feed, in particular in the case of products labelled as ‘local’. The aim of the present research study was to analyse whether the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 38 publications
(46 reference statements)
6
57
0
Order By: Relevance
“…For instance, Gracia (2014) found that Spanish consumers were prepared to pay 9% higher price for fresh lamb with a "locally grown" logo than without [25]. Wägeli et al (2016) revealed that German consumers were willing to pay a price premium of 41-56% for local organic animal products produced with local feed [26]. The rationale behind this motivation is that the production processes are often transparent to consumers and that the short transportation distance ensures the freshness of the foods [27].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Gracia (2014) found that Spanish consumers were prepared to pay 9% higher price for fresh lamb with a "locally grown" logo than without [25]. Wägeli et al (2016) revealed that German consumers were willing to pay a price premium of 41-56% for local organic animal products produced with local feed [26]. The rationale behind this motivation is that the production processes are often transparent to consumers and that the short transportation distance ensures the freshness of the foods [27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The rationale behind this motivation is that the production processes are often transparent to consumers and that the short transportation distance ensures the freshness of the foods [27]. Another reason is that consumers are often included to support the local economy by purchasing foods produced locally [26]. However, a study in the Chinese context revealed that consumers were prepared to pay more for imported than domestic beef, although the willingness to pay for beef imported from countries suffered from bovine spongiform encephalopathy (BSE) outbreak was much lower [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hempel & Hamm () found the same preference order for local food and Wägeli et al . () could likewise determine a higher preference for a local feed origin in comparison to a German feed origin. If all origin options (farm, local, German, EU) are added up, excluding the cases in which an individual chose two or three of these alternatives, the picture changes.…”
Section: Resultsmentioning
confidence: 99%
“…However, Wägeli et al . () found that there is a high potential demand and additional willingness‐to‐pay (WTP) for local food produced with local feed in Germany (Illichmann & Abdulai, ) and in Spain, France and the UK (Font I Furnols et al ., ). Further studies have indicated that consumers are interested in information about animal feeding (Stranieri & Banterle, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation